Rearrangement of a Large Novel Pseudomonas aeruginosa Gene Island in Strains Isolated from a Patient Developing Ventilator-Associated Pneumonia - Singh, G. (American Society for Microbiology, 2014)
Bacterial gene islands add to the genetic repertoire of opportunistic pathogens. Here, we perform comparative analyses of three Pseudomonas aeruginosa strains isolated sequentially over a 3-week period from a patient with ventilator-associated pneumonia (VAP) who received clindamycin and piperacillin-tazobactam as part of their treatment regime. While all three strains appeared to be clonal by standard pulsed-field gel electrophoresis, whole-genome sequencing revealed subtle alterations in the chromosomal organization of the last two strains; specifically, an inversion event within a novel 124-kb gene island (PAGI 12) composed of 137 open reading frames [ORFs]. Predicted ORFs in the island included metabolism and virulence genes. Overexpression of a gene island-borne putative β-lactamase gene was observed following piperacillin-tazobactam exposure and only in those strains that had undergone the inversion event, indicating altered gene regulation following genomic remodeling. Examination of a separate cohort of 76 patients with VAP for integration at this tRNA(lys) recombination site demonstrated that patients exhibiting evidence of integration at this site had significantly higher 28-day mortality. These findings provide evidence that P. aeruginosa can integrate, rapidly remodel, and express exogenous genes, which likely contributes to its fitness in a clinical setting.